ANALISIS PENDAPATAN PEDAGANG SEBELUM DAN SESUDAH PROGRAM REVITALISASI PASAR TRADISIONAL DI KOTA DENPASAR (STUDI KASUS PASAR SUDHA MERTA DESA SIDAKARYA) - Ayuningsasi, Anak Agung Ketut (PIRAMIDA, 2012)
The aim of this study is to analyze the income of the sellers on SudhaMerta market at Desa Sidakarya. The data used are primary data, consisted of thesellers income before and after the market revitalization programm. The result ofthis research shows that the sellers income before and after the marketrevitalization programm are significanly different. In order to improve the incomeof the sellers, it is suggested to fix not only the environment of the traditionalmarket, but also the goods’ distribution, market management, and marketingtechnique.
Keywords: income, market revitalization